2016
DOI: 10.4174/astr.2016.91.3.97
|View full text |Cite
|
Sign up to set email alerts
|

Is focused parathyroidectomy appropriate for patients with primary hyperparathyroidism?

Abstract: PurposeThe aim of this study was to determine whether focused or complete parathyroidectomy was more appropriate and to compare follow-up data in primary hyperparathyroidism (PHPT).MethodsWe retrospectively analyzed 225 operations for PHPT at Yonsei University Health System between 2000 and 2012. After excluding 93 patients, the remaining 132 were divided into 2 groups: those who underwent focused parathyroidectomy (FP) and those who underwent conventional parathyroidectomy (CP). We compared clinicopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…The initial literature search yielded a total of 252 studies, of which 14 , met the inclusion criteria ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial literature search yielded a total of 252 studies, of which 14 , met the inclusion criteria ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 studies, seven were retrospective , six involved collection of prospectively identified items and one did not clarify the type of study. The median MINORS score was 10 of 16 (mean 9·8, range 6–14) for all studies, and the median of the four comparative studies , was 15 of 24 (mean 14·25, range 10–17).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations